Cooling Strategies of Lithium-Ion Battery Pack - A Review - Lazim, Adam Adil; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2024)
Lithium-ion batteries’ physical properties classify them as one of the most important sources of clean energy that overcome the need for fuel usage. The rated operating temperature and its uniformity are of the main demands of Lithium-ion batteries. In this survey, several types of studies have been reviewed with the aim of understanding the thermal management systems used to control the temperature of lithium-ion batteries and their uniformity in the battery pack. They are represented by active and passive systems, as well as the hybrid system, which integrates each of the two mentioned systems into a system to obtain the best thermal performance. Active cooling systems were classified due to the type pf coolant used to air and liquid system, meanwhile passive system classified to PCM and heat pipe system. The survey reveals that the air-cooling of lithium-ion battery pack is better than the use of liquids. About 74% of the reviewed works prefer the use of active strategies. The working temperature under normal conditions should be within -20 to 60 °C, meanwhile the optimum range is 15 to 35 °C. The maximum temperature difference between batteries in the pack is preferred to be 5 °C or less.